Technology options for embedding low-profile electronic components in printed circuit boards - A. A. Efimenko; V. O. Ryabov (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
In order to improve the overall characteristics of printed circuit boards, two technologies for the formation of multilayer printed circuit boards have been developed - with the embedding of low-profile electronic components in a layer of fiberglass and a monolithic layer of polyimide, provided that they are assembled without soldering and welding. The indicators for quantitative evaluation of printed circuit boards with embedded electronic components and their comparison both among themselves and with printed circuit boards without embedded electronic components are proposed.